Using the community-based breeding program (CBBP) model as a collaborative platform to develop the African Goat Improvement Network - Image collection protocol (AGIN-ICP) with mobile technology for data collection and management of livestock phenotypes - Woodward-Greene, M. Jennifer; Kinser, J.M.; Huson, Heather J.; Sonstegard, T.S.; Sölkner, Johann; Vaisman, I.I.; Boettcher, P.; Masiga, C.W.; Mukasa, C.; Abegaz, Solomon; Agaba, Morris; Ahmed, S.S.; et al. (Frontiers Media, 2023)
Introduction: The African Goat Improvement Network Image Collection Protocol (AGIN-ICP) is an accessible, easy to use, low-cost procedure to collect phenotypic data via digital images. The AGIN-ICP collects images to extract several phenotype measures including health status indicators (anemia status, age, and weight), body measurements, shapes, and coat color and pattern, from digital images taken with standard digital cameras or mobile devices. This strategy is to quickly survey, record, assess, analyze, and store these data for use in a wide variety of production and sampling conditions.